The Role of Matrix Metalloproteinase in Human Body Pathologies - Travascio, Francesco (IntechOpen, 2017)
Matrix metalloproteinases (MMPs) are a family of proteolytic zinc-containing enzymes involved in physiological as well as in pathological processes in the human organism. MMPs play a key role in the remodeling of the extracellular matrix. Such a process may occur because of tissue homeostasis, morphogenesis, and tissue repair. However, remodeling could also be a part of many pathological states such as arthritis, cardiovascular diseases, neurodegenerative diseases, or impaired development in congenital anomalies. This book overviews the role of MMPs in different pathologies affecting the human body.